FIRM PERFORMANCE USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA MASA PANDEMIK COVID-19 DI PROVINSI DKI JAKARTA - Siti Mariam; Dhinda Mustika; Muhammad Asrar Ameido (POLITEKNIK LP3I JAKARTA, 2022)
This study aims to see the influence of the Business Environment on the Operating Strategy, and Firm Performance. The research methodology is an explanatory study with a quantitative approach. The population of this study was conducted on Micro, Small and Medium Enterprises (MSMEs) in DKI Jakarta Province, with a total sample of 110 SMEs. Data was collected using a questionnaire and technical data analysis using SEM (Structural Equation Modeling), namely through the smartPLS application. The results of this study are the findings that: (1) the Business Environment affects the Operating Strategy positively and significantly; (2) Business Environment influences Firm Performance negatively and not significantly; (3) Operating Strategy affects Firm Performance positively and significantly; (4) Business Environment influences Firm Performance through Operating Strategy positively and significantly. The results of this study are expected to strengthen the Firm Performance of SMEs in DKI Jakarta Province through the Firm Business Environment and Operating StrategyKeywords: SMEs, Firm Performance, Business Environment, Operating Strategy